Τα προβλήματα που παρεμποδίζουν τους νοσηλευτές για ψυχολογική υποστήριξη σε ασθενείς με καρκίνο του μαστού - Κλεάνθους, Ελισάβετ (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2011)
Introduction: Breast cancer is one of the most frequent cancers among the women population. The patients who experience this sort of incidents, beyond the physical consequences they suffer from the disease, they also show signs of psychological weakness in the continuing of their lives seeking psychological support. Many times, the psychological support role is taken upon on the nurses. Aim: The aim of the degree review is the investigation of the problems which interfere or make hinder nurses to provide psychological support to patients with breast cancer. Material & Method: Through the electronic data bases, “Pub med, Cochrane, Google Scholar and Cinahl”, Greek and International bibliography was inquired using a number of deferent combination of the words “Breast cancer, psychological support, implementation problems, nurses” and the equivalent Greek ones in order to find relevant bibliographical material. From the search, at first 102 articles were found. After that, at the end, the material was studied and 8 articles which were in accordance with the criteria were selected for inclusion in the review. Results: The main cause of the problems nurses faced in providing psychological support was the lack of training and knowledge in issues of cancer and psychological health. At the same time, problems were created by the relations among the nurses with the patients, the relatives of the patients and the personal perceptions of the nurses. Beyond the problems on a personal level, the working load was affecting this significantly as well. Even though under these conditions, the results of such supporting interventions had positive consequences on the enforcement of the patients’ positive psychology. Conclusions: From all the research articles, the conclusion that comes out is that for a proper psychological support of the patients from the nursing staff, subjects need to be introduced in the training program which must focus on oncology and on general psychological support.
Keywords: Breast--Cancer --Psychological aspects; Women patients--Psychology; Breast--Cancer--Nursing